Impact of climate change on hydrometeorological regimes in Northern Ecuador - Carrión Jiménez, Bruna Stefanny (2025)
Climate change has become a major concern for governments worldwide, mainly due to the economy’s dependency on natural resources. The impact of climate change on hydro-meteorological conditions in northern Ecuador for the periods 2041-2070 and 2071-2100 under two emission scenarios RCP 4.5 and 8.5 is studied in this thesis work. Overall, there are consistent signals of an intensification of the hydrological regimes. This is evident by changes in temperature, precipitation, and water discharge patterns. These changes mainly lead to an increment of wet spells which are expected to cause floods during wet seasons, and at a lesser extent an increase of dry spells during dry seasons, the projected seasonal patterns, however, do not show major shifts as compared to current climate. The expected future scenarios under RCP 4.5 or 8.5 indicate that these trends will increase leading to more extreme events. Therefore, the necessity to improve water resource management is imperative. Despite the limited number of hydro-meteorological stations available in northern Ecuador, and the inherent uncertainty of model projections, the projected patterns are consistent among river basins in the three climatic regions, showing similar patterns in both current and projected data. Therefore, the results presented here can be considered as a first approach to estimate water availability for future climate.